Pengaruh Angkatan Kerja dan Investasi terhadap Produk Domestik Regional Bruto di Provinsi Lampung - P. Damianus Feriyandri; Emi Maimunah (Departement of Mathematics Education, 2023)
This study aims to determine the impact of employment, open unemployment, and domestic investment on the economic growth of Lampung Province in Indonesia. The research sample consisted of data from Lampung Province in the first quarter of 2010 to the fourth quarter of 2022. The data source was obtained from the Central Bureau of Statistics of Lampung. Regression analysis using EViews 10 was used to analyze secondary data and time series in this study. This study used a quantitative descriptive approach, which proved to be the most effective method. The results of the study show that the variables of labor, open unemployment, and domestic investment have a significant influence on economic growth. This research is a valuable reference and provides insight for further exploration, helping to understand the impact of employment, open unemployment, and domestic investment on economic growth in Lampung Province.